Stochastic algorithms applied to vortex detections in turbulent flow (Part I) - Marañon Di Leo, Julio (2022)
The need to establish the downwind fluid dynamic field of aerodynamic bodies subjected to a givenvelocity field is well known, to verify their specific aerodynamic characteristics and therefore their efficiency. In this context, different techniques allow us to establish the characteristics of the field, on the one hand, visualizations, which define the qualitative characteristics of it, but it is almost always necessary to carry out quantitative determinations to describe the field correctly, particularly when the field is made up of turbulent wakes, characteristic of aerodynamic bodies under extreme operating conditions. In this sense, in the experimental field and for the definition of the turbulent flow field, it is common to use hot-wire anemometry techniques, which have great capabilities to quantify high-frequency events. Previous work has analysed the determination of changes in hot-wire anemometry signals for the detection of events in turbulent flows with different models, based on numerical algorithms, for the determination of change points (CPM - Change PointModel). The results obtained have shown agreement with conventional methodologies used for thedetermination of turbulent flow characteristics. The present work aims to compare the results obtained previously with the application of new CPM models developed in recent years. Previously applied and evaluated measurements are used, the implementation of the new models is carried out and the results are compared. All the algorithms used can detect changes in data that do not have a known distribution, i.e. non-parametric distributions, which are typical for turbulent flow field signals. The evaluation of measurement signals based on hot-wire anemometry is performed, considering measurements of the fluctuating components of the wind tunnel velocity at a specific point. The signals used correspond to periodic detachments downstream of a flow controldevice (Gurney mini-flap) at the trailing edge of an airfoil. In this way, the determination and characterization of vortices of different types is sought, to validate the different results obtained. The results show which are the best models to use for the experimental detection of such turbulent events in the flow field. These is the first approximation to the evaluation of the complete measurement with different arrange of the mini-flaps, in this case only for the static one.